STRATEGI KOMUNIKASI KEPEMIMPINAN SEBAGAI IMPLEMENTASI KESADARAN BERSIKAP BAGI MUSLIM PADA RANTING IKATAN PELAJAR MUHAMMADIYAH DI SMA MUHAMMADIYAH PRINGSEWU - Julio Salas, Hagi; Marini, Marini (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2023)
In the current era, more and more Islamic missionary organizations are being established, especially among youth or students, with various forms of activities. Through the da'wah-based organization amar ma'ruf nahi munkar, young people or students are directed to call each other to goodness and shun evil. In this organization, it is hoped that young people or students will be aware of their responsibilities as students and as future generations of Muslims. Students who are ready to become agents of change are students who have good personalities by practicing religious values originating from the Qur'an and Sunnah in order to create true Islamic teenagers. In this research the author uses a descriptive research method, which means research that describes variable by variable, one by one. Descriptive research aims to systematically describe the facts or characteristics of a particular population or a particular field in a factual and accurate manner. The problem formulation is: 1) What is the communication strategy for the leadership of the Muhammadiyah Student Association to develop the personality of Muslim students at Pringsewu Muhammadiyah High School? 2) How successful is the personality development of Muslim students at Pringsewu Muhammadiyah High School carried out by the IPM Branch Leaders? Through the Leadership Communication Program in the KDI field and the Cadre field such as KRITING, Kultum, Tadarus, Infak Jum'at, LD and MAPETA, Muhammadiyah Pringsewu High School students have awareness as Muslim individuals and students.